2014
DOI: 10.1089/jpm.2013.0614
|View full text |Cite
|
Sign up to set email alerts
|

Needs, Expectations, and Concerns of Medical Students Regarding End-of-Life Issues before the Introduction of a Mandatory Undergraduate Palliative Care Curriculum

Abstract: Medical students stated a remarkably high interest in learning palliative care competencies. Responding to their specific concerns and needs-especially with regard to the acquisition of emotional coping skills-may be key for the development of successful palliative care curricula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 21 publications
2
13
0
5
Order By: Relevance
“…Previous studies are in agreement with our results, and show that medical students, in general, attribute high importance to palliative care in medicine, PC education, the psychological aspects of it, and learning about symptom control 3 , 4 . However, there appears to be a mismatch between attitudes and the exposure of PC with relatively low clinical and academic exposure to PC noted in medical student curricula 5 , 6 .…”
Section: Introductionsupporting
confidence: 91%
“…Previous studies are in agreement with our results, and show that medical students, in general, attribute high importance to palliative care in medicine, PC education, the psychological aspects of it, and learning about symptom control 3 , 4 . However, there appears to be a mismatch between attitudes and the exposure of PC with relatively low clinical and academic exposure to PC noted in medical student curricula 5 , 6 .…”
Section: Introductionsupporting
confidence: 91%
“…17 % gaben ein hohes Stressniveau (≥7) an [1]. Unter Ärzten, die in onkologischen Abteilungen des Landes Baden-Württemberg arbeiten, gaben lediglich 5,9 % an, dass sie sich durch ihre Berufsausbildung ausreichend gut auf die Begleitung Sterbender vorbereitet sahen [9].…”
Section: Hintergrundunclassified
“…This includes teaching the necessary knowledge as well as providing appropriate teaching methods – for example, discussions in small groups. Previous studies have shown that medical students have a strong interest in ethical questions, but in their opinion, the amount and types of courses available are not sufficient [2], [17]. …”
Section: Introductionmentioning
confidence: 99%